Impact of virtual reality hypnosedation on perioperative pain and anxiety in port implantation under local anesthesia: a randomized controlled pilot trial (VIP Trial) - Steinkraus, Kira Carlotta; Feldmann, Hannah; Hunold, Lisa; Graf, Sandra; Dörr-Harim, Colette; Nasir, Nadir; Michalski, Christoph; Hüttner, Felix (Perioperative medicine, 2024)
Background This monocentric randomized controlled pilot trial investigates the impact of virtual reality (VR) hypnosedation on perioperative anxiety, pain, patient satisfaction, and medication usage during port implantation under local anesthesia. Methods A total of 120 patients undergoing elective port implantation between January 2022 and August 2023 were enrolled and randomized in a 1:1 ratio to either a VR hypnosedation group or a control group. The VR group used a commercially available VR headset with the HypnoVR application, providing various environments, musical back‑grounds, and a guiding voice, while the control group underwent the procedure without VR. Patients with ASA > 3, chronic pain, cognitive issues, and contraindications against VR use were excluded. The main outcomes measured were perioperative pain and anxiety scores, with secondary outcomes including perioperative medication usage. Due to the nature of the interventions, blinding of patients and physicians was not feasible. Statistical analysis was primarily descriptive and exploratory, focusing on estimating effect sizes for future trials. Results The study found no significant differences in immediate postoperative pain with 1.43 ± 1.63 vs. 1.6 ± 2.05 (p = 0.62) or anxiety scores 30.65 ± 9.13 vs. 31.78 ± 13.34 (p = 0.60) between the no VR and VR group, respectively. Additionally, there was a trend to less usage of certain medications, particularly remifentanil (mean dose of 200 mg vs. 100 mg (p = 0.12)) and novaminsulfon (mean dose of 1250 mg vs. 900 mg (p = 0.26)) in the VR group vs. no VR group, respectively. However, these differences were not statistically significant and therefore no definitive conclusions can be drawn regarding medication usage based on this data. Conclusion While VR hypnosedation did not significantly reduce perioperative pain or anxiety in this pilot trial, the observed trends in reduced medication usage suggest potential benefits. These findings warrant further investigation in larger, confirmatory trials to better understand the role of VR in enhancing atient comfort and potentially reducing reliance on pharmacological interventions during surgical procedures.